2004
DOI: 10.1111/j.1600-0870.2004.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of observation impact using the NRL atmospheric variational data assimilation adjoint system

Abstract: An adjoint‐based procedure for assessing the impact of observations on the short‐range forecast error in numerical weather prediction is described. The method is computationally inexpensive and allows observation impact to be partitioned for any set or subset of observations, by instrument type, observed variable, geographic region, vertical level or other category. The cost function is the difference between measures of 24‐h and 30‐h global forecast error in the Navy Operational Global Atmospheric Prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
157
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(158 citation statements)
references
References 10 publications
1
157
0
Order By: Relevance
“…Most NWP centers, which made effective early use of ATOVS (Advanced TIROS (Television and Infrared Observational Satellite) Operational Vertical Sounder), onboard NOAA (National Oceanic and Atmospheric Administration)-15/16/17/18/19, MetOp (The Meteorological Operational satellite A)-A/B and Aqua, have reported a substantial reduction in the forecast root mean square (RMS) error. Adjoint-based estimates of observation impact on NWP (Baker and Daley, 2000) have further demonstrated that the greatest decrease in forecast error is due to Advanced Microwave Sounding Unit-A (AMSU-A), which was launched as part of ATOVS and is used primarily for global atmospheric temperature sounding (Fourrié et al, 2002;Langland and Baker, 2004;Cardinali, 2009;Gelaro et al, 2010). Observations from Microwave Temperature Sounder-1 (MWTS-1) onboard and Fengyun-3B (FY-3B) have positive impacts on NWP forecasts (Lu et al, 2010;Lu and Bell, 2012;Zou, 2013, 2014;Li and Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most NWP centers, which made effective early use of ATOVS (Advanced TIROS (Television and Infrared Observational Satellite) Operational Vertical Sounder), onboard NOAA (National Oceanic and Atmospheric Administration)-15/16/17/18/19, MetOp (The Meteorological Operational satellite A)-A/B and Aqua, have reported a substantial reduction in the forecast root mean square (RMS) error. Adjoint-based estimates of observation impact on NWP (Baker and Daley, 2000) have further demonstrated that the greatest decrease in forecast error is due to Advanced Microwave Sounding Unit-A (AMSU-A), which was launched as part of ATOVS and is used primarily for global atmospheric temperature sounding (Fourrié et al, 2002;Langland and Baker, 2004;Cardinali, 2009;Gelaro et al, 2010). Observations from Microwave Temperature Sounder-1 (MWTS-1) onboard and Fengyun-3B (FY-3B) have positive impacts on NWP forecasts (Lu et al, 2010;Lu and Bell, 2012;Zou, 2013, 2014;Li and Liu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is called the targeted observations technique. Different techniques for the placement of observations in the context of numerical weather prediction models are discussed in [14,90,77,57,88,83,10]. Studies performed during field experiments revealed the potential benefits that may be achieved using adaptive observations as well as various practical issues and shortcomings of the current targeting methodologies.…”
Section: Optimal Placement Of Observationsmentioning
confidence: 97%
“…This may be achieved in a posteriori analysis and data assimilation experiments that are used to provide valuable insight on the benefits and shortcomings of various targeted observations strategies. Langland and Baker use forecasts of different lengths that verify at the same time to define J v and to assess the observation impact on the forecast error [77]. For a priori experimental planning the forecast error at t v is not known when selecting targets (planning stage), nor are the values of future observational data to be assimilated.…”
Section: Optimal Placement Of Observationsmentioning
confidence: 99%
“…The contribution of each observation y o i to any scalar function I(x) of the state vector x is of particular interest, where I(x) represents any metric of interest such as ocean transport, eddy kinetic energy, eddy fluxes, etc. Following Langland and Baker, 9 it is easy to show that the change in I(x) due to assimilating the observations is given by the first-order Taylor expansion:…”
Section: Quantifying the Impact Of The Observations On Ocean Circulatmentioning
confidence: 99%